2002
DOI: 10.1097/00043426-200208000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Ocular Melanoma With High-Dose Interleukin-2 and Thalidomide

Abstract: Uveal melanoma is the most common primary ocular malignancy, although it is rare in children, and patients presenting with metastatic disease have a median survival of only 2 to 5 months. The tumor is generally unresponsive to systemic chemotherapy, but immunotherapy may be effective in selected patients. This report describes an 8-year-old girl with metastatic uveal melanoma treated with high-dose, bolus interleukin-2 (IL-2) and the antiangiogenic agent thalidomide. She tolerated treatment well and initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…BT does, however, provide excellent tumor control, with local control rates exceeding 90% 41. A single-center study of 458 patients with predominantly medium-sized choroidal melanomas treated with 108Ru brachytherapy reported actuarial rates of tumor recurrence to be 1%, 2%, and 3% at 2, 5, and 7 years, respectively 42. Visual outcomes are dependent upon tumor location and thickness, with one large study reporting an actuarial rate of 55% for conservation of vision 20/40 or better at 9 years 43.…”
Section: Treatment Of the Primary Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…BT does, however, provide excellent tumor control, with local control rates exceeding 90% 41. A single-center study of 458 patients with predominantly medium-sized choroidal melanomas treated with 108Ru brachytherapy reported actuarial rates of tumor recurrence to be 1%, 2%, and 3% at 2, 5, and 7 years, respectively 42. Visual outcomes are dependent upon tumor location and thickness, with one large study reporting an actuarial rate of 55% for conservation of vision 20/40 or better at 9 years 43.…”
Section: Treatment Of the Primary Tumormentioning
confidence: 99%
“…However, no clinical trials of IL-2 in metastatic UM have been performed. Soni et al108 reported an 8-year-old girl with UM metastatic to liver and pancreas who was treated with highdose bolus IL-2 and thalidomide. The patient experienced minimal toxicity and had stable disease for 23 months.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Many of the reports of side effects associated with BRM administration have been single case studies [15][16][17][18], used retrospective or cross-sectional designs [19], or used lower dosages of BRMs than is usually used to treat melanoma [20]. None have measured HRQOL associated with high-dose IFN administration in melanoma patients prospectively during Having accurate information on the QOL and toxicities associated with administration of BRMs is important for consideration of these therapies for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports suggested that interleukin-2 administered together with other immune response modifiers might be effective in choroidal melanomas. 54,55 Soni et al reported on an 8-year-old girl with metastatic uveal melanoma who was treated with high-dose bolus IL-2 plus thalidomide that resulted in regression of liver, pancreatic, and pulmonary metastases with control of her disease that lasted for over 3.5 years. 54 Minor et al reported a patient with choroidal melanoma metastatic to the liver treated with interleukin-2 (IL-2), LAK, and interferon who survived over 5 years.…”
Section: Intravenous Chemotherapymentioning
confidence: 99%
“…54,55 Soni et al reported on an 8-year-old girl with metastatic uveal melanoma who was treated with high-dose bolus IL-2 plus thalidomide that resulted in regression of liver, pancreatic, and pulmonary metastases with control of her disease that lasted for over 3.5 years. 54 Minor et al reported a patient with choroidal melanoma metastatic to the liver treated with interleukin-2 (IL-2), LAK, and interferon who survived over 5 years. 55 Agarwala et al reviewed the results of treatment of 39 patients with metastatic uveal melanoma included in IL-2 plus histamine phase 2/3 clinical trials for patients with melanoma.…”
Section: Intravenous Chemotherapymentioning
confidence: 99%